A Temperamental and awkward tree - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
The shea butter tree on average bears fruit every two or three years. Experts have not yet found out the reason for its irregular fruiting cycle. It seems probable that the harmatan and bush fires contribute by killing of the flowers and buds...